Analisis Perbandingan Kinerja Keuangan Daerah Pemekaran di Provinsi Papua - Purba Riani, Ida Ayu; Kaluge, David (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
The objective of study is to compare the financial performance in the extended regions in Papua Province. It is indicated that the host takes a positive benefit after launching the new autonomous region because it will reduce the once consistently fiscal dependence. However, DOB tends to have a stagnant fiscal self-support rather than the host. The optimization of PAD sources at DOB seems lower than the host. Moreover, the ability of DOB to create local revenue may still be better than the control. It is evident during the beginning of extension when DOB shows better fiscal self-support rather than control. DOB’s capital expense is more focused in the investment in the governmental infrastructures such as office building, transportation, office tools and household which are not previously equipped in the new autonomous region. However, the decrement trend is apparent as shown by higher proportion of expense rather than the host and the control. In whole, the result of index comparison indicates that in the beginning of current year. DOB shows the higher local financial performance rather than the host and the control. Unfortunately, it decreases in the last two years of observation, or even lower than the host but not far different from the control. Such condition continues to develop until the end of observation, when the host’s financial performance is getting better than DOB’s and the control’s.Keywords: financial performance, PAD, PDRB